Students’ Perception: Self Confidence on English Speaking Skill - M. Romzi Suja’i; Luh Mila Trisna Dewi; Kadek Heni Oktarina Wisudayanti (STKIP AGAMA HINDU SINGARAJA, 2023)
Generally, problems in self-confidence are experienced by everyone, especially in communication. This study aims to determine the factors of students’ confidence in communicating by using English, especially at SMK NEGERI 3 Singaraja, in the class X DKV 3. This study was designed by using a qualitative descriptive research method. The research subjects were students of SMK Negeri 3 Singaraja, especially in class X DKV 3 using observation instruments for all students and interviews for 20 students. The results of this study indicate that students need to study English more actively, had a dictionary, took an English course and had someone to talk to during practice. In addition, students' perceptions also said that the support of friends and the environment greatly influenced their self-confidence and the relationship between confidence and communication was very closely because when students could communicate by using English well and fluently, then their self-confidence developed and be better.